EFEKTIVITAS PENDEKATAN RME (REALISTIC MATHEMATICS EDUCATION) UNTUK MENINGKATKAN KREATIVITAS BELAJAR SISWA SMP SWASTA ADVENT BARUS - Uswatun Hasanah Sinaga; Marzuki Ahmad; Rahmatika Elindra (JURNAL MathEdu (Mathematic Education Journal), 2022)
Abstract This study aims to know whether RME approach is effective in increasing the learning creativity at the eighth grade students of Barus Adventist Private Junior High School students. The research used an experimental method bu applying one group pretest posttest design. The sample of this study is 35 students which were taken by using the total sampling technique. The data collection techniques used observation and tests. The data collected are analyzed in two stages, namely descriptive analysis and inferential analysis. The research results, it is known that the description of using RME approach is on average 3.00 (good category). Furthermore, the description of student learning creativity before learning RME obtained an average value of 66.21 (enough category) and after learning RME obtained an average of 76.82 (good category). Based on the results of hypothesis testing, it can be known that the value of Sig. (2-tailed) of 0.000 < 0.005. It means that RME approach is effective in increasing the learning creativity of the students of the Barus Adventist Private Junior High School with classical completeness data known to be 65.71% (effective category) and N-Gain obtained 0.46 (medium category).